PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN MELALUI KEPUASAN PELANGGAN TERHADAP MINAT BELI ULANG PADA RUMAH KECANTIKAN SIFRA DI PATI - Resti, Devi; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2016)
Marketing is growing rapidly and understand consumer behavior become one of the success strategies in marketing the product. Produce a product that consumers want will streamline marketing activities, through understanding consumer behavior will be obtained information on how consumers develop a number of alternatives in the interest of using the services again. This information will be the focus of marketing activities for product design, pricing, promotion mix, distribution to the service system in accordance with the consumer through Â the behavior shown. The aim in this study was to analyze the influence of the perception of price and quality of service to customer satisfaction and to analyze the influence of the perception of price, service quality and customer satisfaction on buying interest again. The population in this study is the beauty of the service users home Sifra in Pati, with a total sample of 75 respondents. The sampling technique is acidental Sampling. The type of data used are primary data with questionnaires and secondary data with literature. The analytical tool used is the path analisys. Results from this study are: the perception of price and service quality effect on customer satisfaction, perception of price, quality of service and customer satisfaction influence on buying interest again. Customer satisfaction is an intervening variable between perceptions influence the price and quality of service to re buying interest.